Analyzing Bid and Indicative Prices in Historic Building Reconstructions in the Czech Republic - Hromada Eduard; Brozova Lucie; Heralova Renata Schneiderova; Macek Daniel; Vitasek Stanislav; Strelcova Iveta (Civil and Environmental Engineering)
Valuing the reconstruction of historic buildings is a complex and challenging task due to the unique nature of these structures and the uncertainties involved in estimating the scope of work. This study aimed to bridge the gap between traditional construction practices and modern economic frameworks by developing a comprehensive methodology for the valuation of construction works on historic buildings. Focusing on the Czech Republic, the study analysed the tender budgets of 21 reconstruction projects to be carried out between 2020 and 2023. The analysis compared tender prices with standardised indicative prices to identify significant discrepancies and the reasons for them. The proposed methodology integrated market-based price analysis and traditional pricing tools, providing a robust framework for accurate cost estimation. This approach not only ensured the preservation of the cultural value of historic buildings, but also provided a practical, financially sound strategy for their restoration. The findings of this study provide valuable insights for stakeholders involved in the pricing and budgeting of restoration projects, helping to refine cost estimation methodologies and improve the efficiency and accuracy of budgeting processes.